Monetary Policy Implementation and Volatility Transmission along the Yield Curve : The Case of Kenya - Alper, Emre (IMF Working Papers; Working Paper ;, 2016)
This paper analyzes the degree to which volatility in interbank interest rates leads to volatility in financial instruments with longer maturities (e.g., T-bills) in Kenya since 2012, year in which the monetary policy framework switched to a forward-looking approach, relative to seven other inflation targeting (IT) countries (Ghana, Hungary, Poland, South Africa, Sweden, Thailand, and Uganda). Kenya shows strong volatility transmission and high persistence similar to other countries in transition to a more forward-looking monetary policy framework. These results emphasize the importance of a strong commitment to an interbank rate as an operational target and suggest that the central bank could reduce uncertainty in short-term yields significantly by smoothing out the overnight interest rates around the policy rate.